2016
DOI: 10.4049/jimmunol.1600035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Pharmacology of the NLRP3 Inflammasome Inhibitor CP-456,773 (CRID3) in Murine Models of Dermal and Pulmonary Inflammation

Abstract: A critical component of innate immune response to infection and tissue damage is the NACHT, LRR, and PYD domains–containing protein 3 (NLRP3) inflammasome, and this pathway and its activation products have been implicated in the pathophysiology of a variety of diseases. NLRP3 inflammasome activation leads to the cleavage of pro–IL-1β and pro–IL-18, as well as the subsequent release of biologically active IL-1β, IL-18, and other soluble mediators of inflammation. In this study, we further define the pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
117
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 56 publications
3
117
1
Order By: Relevance
“…MCC950 is a small-molecule able to block canonical and non-canonical NLRP3-induced ASC oligomerization without interfering with NLRC4 and AIM2 activity or TLR signaling (Coll et al, 2015). MCC950 has been shown to be effective for the treatment of CAPS in mice harboring activating Nlrp3 mutations (Coll et al, 2015) and in mouse models of dermal and airway inflammation (Primiano et al, 2016). β-hydroxybutyrate (BHB) is an anti-inflammatory molecule that specifically targets NLRP3 activity.…”
Section: Inhibition Of Il-1 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…MCC950 is a small-molecule able to block canonical and non-canonical NLRP3-induced ASC oligomerization without interfering with NLRC4 and AIM2 activity or TLR signaling (Coll et al, 2015). MCC950 has been shown to be effective for the treatment of CAPS in mice harboring activating Nlrp3 mutations (Coll et al, 2015) and in mouse models of dermal and airway inflammation (Primiano et al, 2016). β-hydroxybutyrate (BHB) is an anti-inflammatory molecule that specifically targets NLRP3 activity.…”
Section: Inhibition Of Il-1 Signalingmentioning
confidence: 99%
“…Small molecule inhibitors were shown to be beneficial in mice models of FCAS and MWS; the anti-inflammatory molecule BHB inhibits constitutive NLRP3 inflammasome activity (Youm et al, 2015). Additionally, the specific NLRP3 inhibitor MCC950 showed efficacy in mouse models of CAPS harboring activating NLRP3 mutations (Coll et al, 2015), and in mouse models for dermal and airway inflammation (Primiano et al, 2016). …”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%
“…Jiang et al (2017) also showed that CY-09 can be used for limiting NLRP3 inflammasome activation in vivo. CY-09 showed favorable in vivo and ex vivo pharmacokinetic properties for stability, safety, and oral bioavailability, resembling those of MCC950/CRID3 (Coll et al, 2015; Primiano et al, 2016; Jiang et al, 2017). MCC950/CRID3 was shown to inhibit NLRP3-dependent pathology in preclinical disease models, including the Nlrp3 Ala350Val-neoR knock-in mouse model of CAPS (cryopyrin-associated autoinflammatory syndromes), the experimental autoimmune encephalomyelitis mouse model of multiple sclerosis, the imiquimod cream–induced mouse model of skin inflammation, and house dust mite–induced acute airway inflammation in mice (Coll et al, 2015; Primiano et al, 2016).…”
mentioning
confidence: 96%
“…CY-09 showed favorable in vivo and ex vivo pharmacokinetic properties for stability, safety, and oral bioavailability, resembling those of MCC950/CRID3 (Coll et al, 2015; Primiano et al, 2016; Jiang et al, 2017). MCC950/CRID3 was shown to inhibit NLRP3-dependent pathology in preclinical disease models, including the Nlrp3 Ala350Val-neoR knock-in mouse model of CAPS (cryopyrin-associated autoinflammatory syndromes), the experimental autoimmune encephalomyelitis mouse model of multiple sclerosis, the imiquimod cream–induced mouse model of skin inflammation, and house dust mite–induced acute airway inflammation in mice (Coll et al, 2015; Primiano et al, 2016). CY-09 also prevented neonatal lethality in the Nlrp3 Ala350Val-neoR knock-in mouse model of CAPS, it improved diabetic symptoms in mice given a high-fat diet and blocked NLRP3-dependent caspase-1 activation and IL-1β secretion from human peripheral blood mononuclear cells (PBMCs) of healthy donors and synovial fluid cells of gouty arthritis patients (Jiang et al, 2017).…”
mentioning
confidence: 96%
See 1 more Smart Citation